Assessment of waste generated from fresh Nile tilapia Oreochromis niloticus in Accra, Ghana - Richard Yaw Otwey; Amy Atter; Christopher Galley; Stephen Nketia; Youngsun Lee; Hanna M. Koivula; Seth K. Agyakwah (Aquaculture, Fish and Fisheries, 2024)
Abstract Aquaculture is a key component of Ghana's food system strategies, promoting sustainable animal protein production. Aquaculture complements traditional marine capture fisheries to close the gap between demand and supply. However, about one third of fish produced globally have been reported to go to waste yearly. Among the various cultured fish, the Nile tilapia Oreochromis niloticus is a predominant species. This study aimed to estimate the extent of Nile tilapia wastage by consumers in Ghana. A web‐based cross‐sectional consumer survey was designed to assess the parts of the tilapia consumers generally classified as edible or inedible, taking into account the three primary tilapia preparation methods. The study utilised a semi‐structured online questionnaire, gathering responses from 246 participants. The parts of Nile tilapia investigated included the flesh, fins, offal, head, scales, bones, and gill flaps/opercula. The analysis of consumed and wasted parts of Nile tilapias by weight showed that, on average, the flesh made up the majority of the fish at 55.26%, followed by the head at 26.46%, offal at 8.51%, scales at 3.10%, fins at 2.93%, bones at 2.76%, and operculum at 0.98%, which was the smallest component. The study concluded that approximately 30%–45% of waste is generated from Nile tilapia in the Ghanaian supply chain. Tilapia was widely consumed by all groups, with an average liking score of 7.69 ± 1.95 on a 10‐point hedonic scale. A significant association was found between gender and consumption patterns with females showing a higher degree of liking. There was a strong association between the method of preparation and consumption patterns; the fried parts were classified as more edible compared to those that were boiled or grilled. To reduce waste in the aquaculture industry, tilapia and other fishes could be processed in a way that various edible and inedible parts are sold separately.